IL‐17 induces cellular stress microenvironment of melanocytes to promote autophagic cell apoptosis in vitiligo. Issue 9 (3rd April 2018) - Zhou, Jia; An, Xiaohong; Dong, Jinjin; Wang, Yichuan; Zhong, Hui; Duan, Lanlan; Ling, Jingjing; Ping, Fengfeng; Shang, Jing
ABSTRACT: Vitiligo is a depigmentary disorder that develops as a result of the progressive disappearance of epidermal melanocytes. Stress can precipitate or exacerbate a skin disease through psychosomatic mechanisms. Stress exposure induces vitiligo‐like symptoms in mice, as cellular damage to melanocytes causes synthetic pigment loss. Stress also increases IL‐17, IL‐1β, and antimelanocyte IgG in model mouse serum. Up‐regulation of the IL‐1β transcript in patients suggests its possible role in autoimmune pathogenesis of vitiligo. We demonstrate that IL‐17 promoted IL‐1β secretion from keratinocytes. Mitochondrial dysfunction, which can induce the excessive production of reactive oxygen species (ROS), is emerging as a mechanism that underlies various inflammatory and autoimmune diseases. In this study, we demonstrate that IL‐17 inhibits melanogenesis of zebrafish, normal human epidermal melanocytes, and B16F10 cells. IL‐17 increased mitochondrial dysfunc‐tion and ROS accumulation, which was related to autophagy induction. Autophagy is needed for autophagic apoptosis of B16F10 cells induced by IL‐17. To inhibit ROS generation, B16F10 cells were pretreated with N ‐acetyl‐L‐cysteine (NAC), which inhibited autophagy. 3‐Methyladenine (3‐MA) also had an inhibiting effect on autophagy. NAC or 3‐MA pretreatments inhibited IL‐17‐mediated cell apoptosis. In summary, IL‐17 induces the cellular stress microenvironment in melanocytes to promote autophagic cell apoptosis in vitiligo.—Zhou, J., An, X., Dong, J., Wang, Y., Zhong, H., Duan, L., Ling, J., Ping, F., Shang, J. IL‐17 induces cellular stress microenvironment of melanocytes to promote autophagic cell apoptosis in vitiligo. FASEB J. 32, 4899–4916 (2018). www.fasebj.org